Determination of ghrelin structure in the barfin flounder (Verasper moseri) and involvement of ingested fatty acids in ghrelin acylation - Kaiya, Hiroyuki; Andoh, Tadashi; Ichikawa, Takashi; Amiya, Noriko; Matsuda, Kouhei; Kangawa, Kenji; Miyazato, Mikiya (Frontiers in Endocrinology, 2013)
Ghrelin is a peptide hormone that is acylated with a fatty acid, usually n-octanoic acid, at the third amino acid residue (usually a serine or threonine), and this acylation is known to be essential for ghrelin activity not only in mammals but also in non-mammals, such as fish. However, the modification mechanisms of ghrelin modification in fish are not known. In this study, we elucidated the structure of ghrelin in a teleost, the barfin flounder (Verasper moseri), and determined whether ingested free fatty acids of various chain lengths participated in ghrelin acylation. Complementary DNA cloning revealed the barfin flounder prepro-ghrelin to be a 106-amino acid (aa) peptide and the mature ghrelin to be a 20-aa peptide (GSSFLSPSHKPPNKGKPPRA). However, purification of ghrelin peptides from stomach extracts demonstrated that the major form of the hormone was a 19-aa decanoylated peptide (GSS[C10:0]FLSPSHKPPNKGKPPR) missing the last alanine of the 20-aa peptide. Ingestion of feed enriched with n-heptanoic acid (C7), n-octanoic acid (C8), or n-nonanoic acid (C9) changed the modification status of the peptide: ingestion of C8 or C9 increased the amount of C8:0 or C9:0 19-aa ghrelin, respectively, but no C7:0 ghrelin was isolated after ingestion of C7. These results indicate that ingested free fatty acids are substrates for ghrelin acylation in the barfin flounder, but the types of free fatty acids utilized as substrates may be limited.